Stereo vision for blind people with low cost cameras (AACINI - International Journal of Industrial Engineering, 2021)
This work presents the advancement of the design of a stereo vision equipment with low-cost cameras capable of detecting objects within a room, to facilitate the mobility of blind people within it, avoiding accidents with an object present. With this equipment, the aim is to achieve a better social integration of the blind person, increasing their expectations in terms of mobility and freedom of action. It has been shown that these technologies favor the participation of the blind person in the close family environment and also that it has an important psychological scope from the emotional point of view. In addition, it increases the possibilities that institutions related to this subject have by having active technologies that allow a greater scope for the effective care of the people who attend. The use of this equipment significantly reduces accidents that may occur when the blind person collides with existing objects when moving and serious injuries may occur. In this way, the problem of the person with visual impairment, is approached in a more inclusive way, where not only attention is focused on them exclusively, but also includes the closest family group and the institutions that treat this situation.
Keywords: Visual disability; Social integration; Person; Low cost; Cameras